Leader’s Point of View on Factors Contributed to Surakarta’s Customs Office Performance - Mubarok, Aulia Achyar; Maharani, Anita; Hidayah, Zainur (Universitas Pendidikan Indonesia (UPI), 2024)
This research aims to examine and explore what steps were taken by Surakarta Customs and Excise to achieve organizational targets during that period. This research uses an exploratory method with a qualitative approach. Data sources come from direct observation activities in the field, the results of in-depth interviews with sources/informants as well as documentation in natural settings. The researcher is the main instrument of analysis in this research. The data obtained was analyzed and visualized using NVIVO software to help present raw data that had been organized according to the researcher's needs. The analysis stages using NVIVO software begin with; (1) import data, (2) data coding, (3) data classification, and (4) data display. This research found that there are several factors that influence organizational performance, both individual factors and organizational factors themselves. Individual-level factors such as employee performance and perceived organizational support. Meanwhile, organizational-level factors such as risk management monitoring, implementation of learning organizations, transformational leadership, and strong implementation of organizational values have been proven to influence organizational performance.